046 Age–QRST angle score differentiates survival and predicts early and late mortality in 1843 ACS patients. (22nd September 2015) - Lown, M T; Gale, C P; Munyombwe, T; Hall, C; Morrell, C; Jackson, B; Sapsford, R J; Das, R; Kilcullen, N; Barth, J; Pepper, C B; Hall, A S
Abstract : Introduction: Accurate and rapid risk assessment is central to the management of patients presenting with acute coronary syndromes (ACS). Simple data from the resting 12-lead electrocardiogram (ECG) is immediately available at first medical contact and may help predict mortality. Methods: We regressed 30-day and 2-year mortality on simple ECG variables and clinical characteristics available during admission in 1843 patients with ACS in the EMMACE 2 cohort to generate a parsimonious model that was validated in 550 ACS patients from the EMMACE 1 cohort. The absolute difference between the frontal QRS and frontal T wave axis was calculated as (T wave axis – QRS axis) and if greater than 180 degrees was subtracted from 360, to give a continuous variable between 0 and 180 degrees. Association between mortality and potential predictor factors were quantified by ORs with 95% CIs. An age-QRST angle score was developed and its discriminative performance assessed using the C-statistic. Cox proportional hazards was used to generate survival models, and experiences analysed using Kaplan–Meier estimates. Results: The mean (SD) age was 70.1 (13.1) years; and 1547 (61.9%) were male. Of the cohort 942 (37.7%) were non ST-elevation myocardial infarction (NSTEMI), 755 (30.2%) were STEMI and 802 (32.1%) were troponin negative ACS. After adjustment for age, heart failure, previous AMI, heart rate, systolic BP, ST depression, creatinine, elevated cardiac markers and inpatient PCI, the QRS-T angle carried the greatest significance of the ECG parameters. Age-QRST angle score powerfully discriminated 30-day and 2-year mortality (C statistic 0.74, 95% CI 0.71 to 0.78) and 2-year (C statistic 0.76, 95% CI 0.74 to 0.78) mortality, and maintained its performance in the EMMACE-1 validation cohort (C statistic 0.79, 95% CI 0.75 to 0.83) at 30-days and (C statistic 0.76, 95% CI 0.71 to 0.8) at 2-years. Significant differences in survival experience for 2 year survival were evident by age-QRST angle score (Score 0=3.7%, Score 1=14.4%, Score 2=30.2%, Score 3=38.2%, Score 4=57.3%) (Abstract 46 Figure 1 ). Conclusions: Our results indicate that a wide frontal plane QRS-T angle is strongly predictive of mortality and long-term survival following ACS. The proposed model has several advantages over other risk scores in that it is parsimonious, objective (requiring no ECG interpretation) and rapidly available and thus truly near-point.